Meningkatkan Hasil Belajar PAI Menggunakan Metode Diskusi Siswa Kelas IV SDN 09 Sentosa Padang Gelugur - Nikmalianti, Nikmalianti (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aimed to improve the learning outcomes of Grade IV students at SDN 09 Sentosa Padang Gelugur in Islamic Education (PAI) by implementing audio-visual media. The research method used was classroom action research (CAR) consisting of two cycles, each involving planning, implementation, observation, and reflection. The results showed that using audio-visual media could enhance students' learning outcomes. In the pre-cycle stage, the students' learning mastery reached only 47%. After Cycle I, the mastery increased to 53%, and in Cycle II, it reached 66.67%. Although there was a significant improvement, the students' learning outcomes did not meet the expected success indicator of 75%. This study concludes that audio-visual media is an effective method to enhance students' learning outcomes but requires further refinement to achieve optimal results